TECHNOLOGIES OF 3D-PRINTING IN THE EDUCATIONAL PROCESS - I. G. Mayorov; A. B. Belsky (Цифровая трансформация)
The article touches upon the topic of using 3D-printing technologies in education. 3D-printing technologies can be used to teach technological skills in engineering and design as the main tool. They also help to reorient attention from the digital or virtual environment to the real world, because as a result of learning activity, not sketches and layouts, but real objects with specified characteristics act. 3D-printing technologies are fast-developing and promising technologies that can find their application in various fields, including in the field of education. These technologies due to the appearance of personal printing devices can facilitate the introduction of new forms of organization of the educational process, increase the motivation and formation of the necessary competencies of graduates and teachers.